The Role of Women in Village Development in Dusun 001 Pasar Pedati Village, Pondok Kelapa Sub-District, Bengkulu Tengah Regency - Risdiyanto, Bayu; Murwani, Anis Endang Sri; Lorita, Evi; Imanda, Antonio; Amin, Bando; Wahyudi, Agusman; Putri, Rahayu; Popytasari, Popytasari; Ferdinand, M. (UKInstitute, 2021)
This community service project aims to enhance the role of women in village development, particularly in Dusun 001, Pasar Pedati Village, Pondok Kelapa Sub-district, Central Bengkulu Regency. The program stems from the awareness of women's contributions to non-physical development such as family economy and education, as well as underutilized local potential. Through observation, interviews, and group discussions, the project identified key issues faced by local women, including limited distribution access for MSME products, lack of digital literacy, and high rates of early marriage. The outcomes include recommendations for training programs, digital media utilization, and scholarship information sharing. This activity is expected to be the starting point for sustainable, locally-based women empowerment